A determination of the main regulators of necroptosis in testicular tissue under different heat stresses - Tatar, Musa; Tüfekci, Kıymet Kübra; Uslu, Sema (Springer Science and Business Media LLC, 2025)
Although minimal increases in testicular temperature can compromise spermatogenesis and lead to fertility-related problems, the basic mechanism involved in germ cell destruction as a response to heat stress is still unclear. However, necroptosis is known to regulate a number of physiological and pathological events. This study investigated the role of RIPK1/RIPK3 and MLKL, the main regulators of necroptosis, against different heat stresses in testis tissue. Forty-two Wistar albino rats were divided into seven groups: six experimental exposed to heat stress and one control. Heat stress was induced by causing the rats to swim for 30 min daily for 60 days in a water bath at temperatures of 39 °C and 43 °C. Testis tissues were collected while the animals were under anesthesia on the 1st, 7th, and 14th days after 60 days of heat application. The tissues were first fixed in Bouin's solution. After routine histological procedures, immunohistochemical staining was performed on one-half of the tissues using RIPK1/RIPK3 and MLKL primary antibodies on serially collected 5 μm-thick sections. Immunoblotting analysis was performed on the other half. Analyses revealed an increase in the expression of RIPK1/RIPK3 and MLKL proteins, regulators of necroptosis, in both the 39 °C and 43 °C groups, although this was greater in the tissue exposed to 43 °C heat stress. These molecules were also especially affected by round and elongated spermatids, and reactivity was observed in Leydig cells. In conclusion, exposure to increased temperature may cause RIPK1/RIPK3 and MLKL-mediated cellular changes in the testis.
Keywords: Male; Infertility; Receptor-Interacting Protein Serine-Threonine Kinases; Necroptosis; Testis; Animals; Rats, Wistar; Spermatogenesis; Protein Kinases; Heat stress; Heat-Shock Response; Rats